Tingkat Pengetahuan dan Kesadaran Masyarakat Akan Deteksi Kanker Serviks di Lingkungan RW 12 Pondok Wage Indah 2 Sidoarjo - Hernanda, Pratika; Wardhani, Mira Kusuma; Rahmawati, Febtarini; Agusaputra, Harman (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2023)
Introduction: Cervical cancer is a malignant tumor that attacks the surface layer of the cervix, called squamous epithelial cells, which are located between the uterus and the vagina. It is important for women to know what factors can cause cervical cancer and have knowledge about preventing cervical cancer because the incidence of cervical cancer is still high in Indonesia, and there are still many women who lack knowledge. Method: A descriptive research design with a sample size of 33 people used total sampling of respondents who underwent pap smear examinations during Early Detection of Cervical Cancer event in RW 12 - Pondok Wage Indah 2 Sidoarjo. The data will be analyzed with a quantity test using SPSS software. Results: This research shows that the average age of respondents iss 48 years, as many as 47.2% of respondents have high education (minimum D3), the majority are housewives (IRT) as many as 25 people (69.4%), and the majority 23 people (63.9%) had good knowledge of cervical cancer risk factors, 9 people (25%) had sufficient/moderate knowledge and 1 person (2.8%) had poor knowledge. Conclusion: Respondents who underwent pap smear examinations mostly had a good level of knowledge about cervical cancer.